If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying f(x) = 2x + 5 Multiply f * x fx = 2x + 5 Reorder the terms: fx = 5 + 2x Solving fx = 5 + 2x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = 5x^{-1}+ 2 Simplifying f = 5x^{-1}+ 2 Reorder the terms: f = 2 + 5x^{-1}

| 2x(8-2y)+y=7 | | 28=3+2x | | -24(-3)= | | 6+4s-2=9s+12-7s | | n/6-1=10 | | f(x)=-3x+1 | | -14(5)= | | 9x-5=27x+1 | | 25(-30)= | | -6n-30=-2n+4(1-3n) | | y=-x^2-5x-6 | | 6z^2-13z+6=0 | | -2(-5)(4)= | | 2x+8+2x-4=3x+12 | | 150(-4)= | | -5-6=-y-3+2y | | (u+1)(u+5)=0 | | -200(-75)= | | -8(0)(7)= | | 5(y-4)=30 | | -3g+6+2g=16 | | 23.9=d-14.25 | | 2x^2+60x+25=0 | | X=-5+0.75y | | 5X^2+15X-1=0 | | 41=-5+10x | | 112=7(-4-4x) | | 3.6x-8.5=12.4 | | X^3-4x^2-3x=0 | | 2n+15=2n+20 | | 4(x+13)=1 | | 8/15=4a/a+b | | 5a-60=24a+16 | | -1.2m+1.25=0.77 | | 32+4m=-3(-5m-2) | | x-2x/3+4=-3/4(2x-1) | | (4y-18/3)(6/6y-27) | | 40=-2(7+3b)+6(1-7b) | | 5/6-2x=11/3+5x | | 2x^2+15x-398=0 | | 3-4d=d | | 6x+4y=72fory | | 0=-x^2+9x | | -3(-5m-2)=32+4m | | 6+6x=8x | | 167+129=x | | 2m-21=24 | | -5r+11=-6r+8+2 | | 6x+3=9x+9 | | (5-3x/3)+3=2x+1/6 | | -8v+28=-4(v-2) | | c-(-3)=4 | | -4(8a-5)=-4a-36 | | -166-10x=74-2x | | 2y-3=-17 | | 2*-13= | | ((x^2-3x+2)/(x^2+5x+6))*((x+2)/(4x-4)) | | 7.7/0.7 | | -7x+5(x-8)=-28 | | 20/8=34/10 | | 5x^2+35x+30= | | 6a+4+2a= | | 3(5-3x)=-3(5+4x) | | 0.3x+0.7=2 | | 22x+41=5x-10 |